Overview of the quality of life of meningioma patients operated at Dr. M. Djamil Padang year 2019 - Nurwiyeni Nurwiyeni; Rifkind Malik; Diah Rahmawati (Institute of Computer Science (IOCS), 2023)
Meningioma is a primary brain tumor originating from leptomeningen meningothelial (arachnoid) cells. These tumors can occur anywhere along the path of the arachnoid cells, are usually attached to the inner surface of the dura mater and are generally slow growing. Treatment of meningioma patients that lasts a long time has a high morbidity effect, usually leading to a weak condition and even depression. The suffering will encourage the patient to determine attitude. This will affect the quality of life of the patient itself. The purpose of this study was to describe the quality of life of meningioma patients who were operated on at Dr. M. Djamil Padang in 2019. The scope of this research is neuro-psychiatry and neurosurgery. Research was conducted in July 2021. The type of research is descriptive categorical. The reachable population in the study were meningioma patients at Dr. M. Djamil Padang in 2019 as many as 30 samples using the total sampling technique. Univariate data analysis was presented in the form of a frequency distribution and data processing using the computerized SPSS program IBM version 25.0. The results of this study explained that the most age was 45-64 years, namely 18 people (60.0%), the most sex was female, namely 17 people (56.7%), the most family history was none, namely 22 people (73.3 %), and the most quality of life is bad, namely 20 people (66.7%). The conclusion of this study is that the most age is 45-64 years, the most gender is female, the most family history is non-existent, and the most quality of life is poor.